Application Features of Thyristor Regulators to Control the Light Flux in Industrial Fishing - Matafonova E.P. (EDP Sciences, 2021)
To control the intensity of the light flux when fishing saury it is necessary to widely change the voltage of the lighting fishing equipment. It is reasonable to carry out this by controlling additionally installed thyristor regulators supplying individual symmetric three-phase groups of light sources that will ensure balanced loading of the synchronous generator stator windings. In this research the features of using a thyristor voltage regulator in a four-wire system of ship power supply are studied based on mathematical analysis, conclusions are made using computer modeling and the use of current limiting reactors is justified.